MRI of cystic fibrosis lung manifestations: sequence evaluation and clinical outcome analysis. Issue 9 (September 2017) - Scholz, O.; Denecke, T.; Böttcher, J.; Schwarz, C.; Mentzel, H.-J.; Streitparth, F.; Maurer, M.H.; Pfeil, A.; Huppertz, A.; Mehl, A.; Staab, D.; Hamm, B.; et al.
Abstract : Aim: To evaluate different magnetic resonance imaging (MRI) sequences for diagnosis of pulmonary manifestations of cystic fibrosis (CF) in comparison to chest computed tomography (CT), including an extended outcome analysis. Materials and Methods: Twenty-eight patients with CF (15 male, 13 female, mean age 30.5±9.4 years) underwent CT and MRI of the lung. MRI (1.5 T) included different T2- and T1-weighted sequences: breath-hold HASTE (half Fourier acquisition single shot turbo spin echo) and VIBE (volumetric interpolated breath-hold examination, before and after contrast medium administration) sequences and respiratory-triggered PROPELLER (periodically rotated overlapping parallel lines with enhanced reconstruction) sequences with and without fat signal suppression, and perfusion imaging. CT and MRI images were evaluated by the modified Helbich and the Eichinger scoring systems. The clinical follow-up analysis assessed pulmonary exacerbations within 24 months. Results: The highest concordance to CT was achieved for the PROPELLER sequences without fat signal suppression (concordance correlation coefficient CCC of the overall modified Helbich score 0.93 and of the overall Eichinger score 0.93). The other sequences had the following concordance: PROPELLER with fat signal suppression (CCCs 0.91 and 0.92), HASTE (CCCs 0.87 and 0.89), VIBE (CCCs 0.84 and 0.85) sequences. In the outcome analysis, the combined MRI analysis of all five sequences and a specific MRI protocol (PROPELLER without fast signal suppression, VIBE sequences, perfusion imaging) reached similar correlations to the number of pulmonary exacerbations as the CT examinations. Conclusion: An optimum lung MRI protocol in patients with CF consists of PROPELLER sequences without fat signal suppression, VIBE sequences, and lung perfusion analysis to enable high diagnostic efficacy and outcome prediction. Highlights: An optimum lung magnetic resonance imaging (MRI) protocol for the diagnosis of cystic fibrosis (CF) consists of PROPELLER (Periodically rotated overlapping parallel lines with enhanced reconstruction) sequences without fat signal suppression (acquired by respiratory navigator triggering), T1-weighted sequences before and after contrast medium administration, and perfusion analysis. As computed tomography, lung MRI can also function as a surrogate marker to assess the severity of CF lung manifestation and as a potential outcome predictor as well as a tool for treatment monitoring, if an optimized MRI protocol is used. The use of fat signal suppression in the T2-weighted PROPELLER technique, which results in longer acquisition times, does not show substantial benefits compared to PROPELLER sequences without fat signal suppression in the diagnosis of CF lung manifestations.